SteE Enhances the Virulence of Salmonella Pullorum in Chickens by Regulating the Inflammation Response - Liu, Zhike; Wang, Li; Yu, Yan; Fotin, Anatoliy; Wang, Qiuxia; Gao, Pei; Zhang, Yanhong; Fotina, Tetiana; Ma, Jinyou (Frontiers in Veterinary Science, 2022)
Salmonella enterica serovar Pullorum (S. Pullorum) is a host-specific pathogen, which causes acute gastroenteritis with high mortality in poultry. However, the association between steE, encoded by type III secretion system 2, and Salmonella virulence is not well understood. To elucidate the functions of steE in S. Pullorum, ΔsteE strain was constructed using the λ-Red recombination technology. Compared to that in the wild-type, the deletion of steE in S. Pullorum reduced bacterial invasion, proliferation, and late apoptosis in the infected HD-11 cells. In addition, we analyzed the mRNA expression levels of effector genes and cytokines by qRT-PCR. SteE was associated with the regulation of various effector genes and inflammatory cytokines in HD-11 cells during S. Pullorum infection. The wild-type effector steE promoted the expression of anti-inflammatory cytokines (IL-4 and IL-10) and reduced that of pro-inflammatory cytokines (IL-1β, IL-6 and IL-12) compared to that in the ΔsteE-infected HD-11 cells and chicken spleens. Results from the chicken infection model showed that the deletion of steE resulted in significantly decreased colonization and long-term survival of the bacteria and alleviated pathological lesions compared to those in the wild-type. Further, steE increased the virulence of S. Pullorum in chickens by regulating the expression of inflammatory cytokines. Our findings provide insights into the persistent infection and autoimmunity associated with steE in S. Pullorum.